Development of a bait and baiting system for the oral delivery of rabies vaccine to free-ranging African wild dogs (Lycaon pictus) - Du Toit, J.T. (University of Pretoria, 2013)
Dissertation (MSc (Zoology))--University of Pretoria, 2001.